Learning Concurrency in Kotlin: Build Highly Efficient and Scalable Applications - Castiblanco Torres, Miguel Angel (Packt Publishing, Limited, 2018)
The requirements of modern day applications are scalability, speed and making the most use of hardware. Kotlin provides immense support for concurrency. This book addresses the challenges for the design and implementation of concurrent code and shows you how to write lock-free concurrent code taking advantage of Kotlin's concurrency support.